Community-Based Intervention through Posyandu Cadre Training and Assistance for Mothers Under Five to Reduce Stunting in Genaharjo Village, Tuban - Puspitadewi, Teresia Retna; Juliana Christyaningsih; Nurul Hindaryani; Yasin Wahyurianto (Frontiers in Community Service and Empowerment, 2025)
Nutrition problems are still a major public health challenge, especially stunting which has a long-term impact on child growth and development. Based on the 2022 report of the TubanRegency Health Office, the prevalence of stunting in the work area of the Kawa Health Center reached 24.43%. Genaharjo Village is the focus of attention because the number of stunted toddlers has increased from 40 children (2023) to 45 children (14%) in 2024, while 66.7% of pregnant women are at high risk of experiencing Chronic Energy Deficiency (CED). This condition shows the need for intervention to support the achievement of the national target of reducing stunting by 14%. This Community Service aims to evaluate pre-post changes in the knowledge of cadres and mothers of toddlers, anthropometric skills of cadres and the processing of toddler menus by mothers after a two-session intervention in Genaharjo". The activity was carried out in August-September 2025 with evaluation through pre-test and post-test for knowledge, observation of cadre skills, assessment of mothers' ability in food processing, and urine examination of toddlers using the pyridinium crosslink rapid test. The results showed an increase in cadre knowledge from an average of 9.25 to 11.25 and mothers of toddlers from 9.6 to 11.1. Cadres are able to perform anthropometric measurements correctly, while mothers of toddlers are skilled in planning menus and processing 20 nutritious recipes based on local ingredients. Of the 20 urine samples of stunted toddlers, two showed positive results. This intervention is effective in increasing community capacity, but a comprehensive approach is needed including nutrition education, health monitoring, and sanitation improvement for the sustainability of stunting prevention.